E-Government Training to Increase Community Participation - Soleh, Mukhammad; Ikhwaningrum, Dian Utami; Ayuni, Sinda Eria; Putra, Marsudi Dedi; Firmanto, Bayu; Refangga, Galih Setyo (Universitas PGRI Semarang, 2024)
Village E-Government is the implementation of village government through the use of the internet and computers, which is very important as a means of community participation and accountability of the village government for the administration of Government. The method used was to conduct training on Sukopuro village officials who were responsible for website management. The training included an introduction to making emails, making Google forms, and introducing how to accommodate community input from the Google form to the Sukopuro Village Government website. The results of this activity were very positive and received a good response from the Village because it increased knowledge and ability to organize the web and make Google Forms as a means of accommodating community participation in village development in the context of implementing the Sukopuro Village Government E-Government. The understanding of Sukopuro Village village officials about E-Government increased from 20% to 80%. The community has the opportunity to increase their participation in village development and the determination of Village government public policies through Google forms and websites in the Village.